2016
DOI: 10.1016/j.nlm.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity α4β2 nicotinic receptors mediate the impairing effects of acute nicotine on contextual fear extinction

Abstract: Previously, studies from our lab have shown that while acute nicotine administered prior to training and testing enhances contextual fear conditioning, acute nicotine injections prior to extinction sessions impair extinction of contextual fear. Although there is also strong evidence showing that the acute nicotine’s enhancing effects on contextual fear conditioning require high-affinity α4β2 nicotinic acetylcholine receptors (nAChRs), it is unknown which nAChR subtypes are involved in the acute nicotine-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…Subjects were observed every 10 sec for a duration of 1 sec and scored as active or freezing (Blanchard and Blanchard 1972). Following the background contextual fear conditioning procedure used in our previous studies Kutlu et al 2016), in Experiment 1, mice received contextual fear conditioning training, in which they were first placed in the conditioning chambers and baseline freezing was assessed for 120 sec, and then the mice received two white noise-foot shock pairings where the offset of the white noise coincided with the offset of the 2-sec foot shock. (see Fig.…”
Section: Behavioral Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were observed every 10 sec for a duration of 1 sec and scored as active or freezing (Blanchard and Blanchard 1972). Following the background contextual fear conditioning procedure used in our previous studies Kutlu et al 2016), in Experiment 1, mice received contextual fear conditioning training, in which they were first placed in the conditioning chambers and baseline freezing was assessed for 120 sec, and then the mice received two white noise-foot shock pairings where the offset of the white noise coincided with the offset of the 2-sec foot shock. (see Fig.…”
Section: Behavioral Proceduresmentioning
confidence: 99%
“…In addition, there is evidence showing that acute nicotine intake increases the likelihood of intrusive traumatic memories in healthy nonsmokers (Hawkins and Cougle 2013). Moreover, evidence from multiple animal studies showed that acute nicotine enhances contextual fear learning (Gould and Higgins 2003;Gould and Lommock 2003;Davis et al 2006) and disrupts extinction of fear memories Kutlu et al 2016; for review, see Kutlu and Gould 2015). Therefore, given the higher rates of smoking initiation in PTSD patients, the period of acute nicotine intake following a traumatic event may be especially critical for the development and relapse of fear in PTSD.…”
mentioning
confidence: 99%
“…Injection volumes were 10 mL/kg as in previous studies (e.g., Kutlu & Gould 2014). The 0.18 mg/kg dose of acute nicotine was chosen based on our previous reports showing impaired contextual fear extinction at this dose (Kutlu & Gould, 2014; Kutlu et al, 2016a). For the subsequent western blotting experiments, the same dose of nicotine or saline was administered i.p.…”
Section: Methodsmentioning
confidence: 99%
“…The dissection time point was chosen based on a previous report from our laboratory examining acute nicotine’s effects on ERK1/2 phosphorylation during contextual fear conditioning (Gould et al, 2014). We examined ERK1/2 and JNK1 activation at the end of the 1 st and 3 rd extinction day based on our previous studies showing that the effect of nicotine is the largest on the 3 rd day of extinction as the saline group usually shows complete extinction by that day (Kutlu & Gould, 2014; Kutlu et al, 2016a). Therefore, the 1 st extinction day analysis served as a control as we did not expect to see a large difference in terms of long-term memory-associated kinase activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation